2009
DOI: 10.1103/physrevlett.103.057003
|View full text |Cite
|
Sign up to set email alerts
|

Spin Polarization of Half-Quantum Vortex in Systems with Equal Spin Pairing

Abstract: We present a variational analysis for a half-quantum vortex (HQV) in the equal-spin-pairing superfluid state which, under suitable conditions, is believed to be realized in Sr2RuO4 and 3 He-A. Our approach is based on a description of the HQV in terms of a BCS-like wave function with a spin-dependent boost. We predict a novel feature: the HQV, if stable, should be accompanied by a non-zero spin polarization. Such a spin polarization would exist in addition to the one induced by the Zeeman coupling to the exter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 16 publications
0
75
0
Order By: Relevance
“…For this, small samples are necessary in order to reduce the spin-current energy of the HQF state, as pointed out by Chung et al [25]. The role of the Zeeman field to lower the kinetic energy of a HQF state is discussed by Vakaryuk and Leggett [26]. Accordingly, a transition from IQF to HQF is expected to occur with increasing in-plane field, with free-energy minima for the HQF states appearing in the middle of neighboring IQF states [ Fig.…”
mentioning
confidence: 99%
“…For this, small samples are necessary in order to reduce the spin-current energy of the HQF state, as pointed out by Chung et al [25]. The role of the Zeeman field to lower the kinetic energy of a HQF state is discussed by Vakaryuk and Leggett [26]. Accordingly, a transition from IQF to HQF is expected to occur with increasing in-plane field, with free-energy minima for the HQF states appearing in the middle of neighboring IQF states [ Fig.…”
mentioning
confidence: 99%
“…A HQV is also expected to be present in BEC of alkali atoms [6][7][8] and spin-triplet superconductors [9][10][11], among other physical systems. In spite of extensive theoretical [12][13][14] and experimental [15,16] research on HQV in superfluid 3 He since then, its existence is yet to be experimentally confirmed.…”
Section: Superfluidmentioning
confidence: 99%
“…A HQV is also expected to be present in BEC of alkali atoms [6][7][8] and spin-triplet superconductors [9][10][11], among other physical systems. In spite of extensive theoretical [12][13][14] and experimental [15,16] research on HQV in superfluid 3 He since then, its existence is yet to be experimentally confirmed.Recently, we investigated a rotating superfluid 3 He in a slab geometry under a strong magnetic field [17], in which we have shown that a HQV is energetically stable compared to a singular vortex (SV) in the A 2 -phase side (i.e., lower temperature side) in the vicinity of the A 1 -A 2 phase boundary. In this part of the phase diagram, a HQV will nucleate first as the angular velocity of the rotation is increased from zero.…”
mentioning
confidence: 99%
“…(1), may contain terms describing kinetic energies of charge and spin currents 20 , spin-orbit interaction energy 21 , effects of kinematic spin polarization 22 etc. In London theory the free energy of a superconductor is approximated by the kinetic energy of supercurrents described by superfluid velocity v s .…”
Section: Surface Representation Of the Gibbs Potential For A Chimentioning
confidence: 99%